2017
DOI: 10.1111/aas.12931
|View full text |Cite
|
Sign up to set email alerts
|

Are severely injured trauma victims in Norway offered advanced pre‐hospital care? National, retrospective, observational cohort

Abstract: BackgroundStudies of severely injured patients suggest that advanced pre‐hospital care and/or rapid transportation provides a survival benefit. This benefit depends on the disposition of resources to patients with the greatest need. Norway has 19 Emergency Helicopters (HEMS) staffed by anaesthesiologists on duty 24/7/365. National regulations describe indications for their use, and the use of the national emergency medical dispatch guideline is recommended. We assessed whether severely injured patients had bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…However, while population data are fairly stable, the same does not hold for incident data. The yearly reports on HEMS missions indicate that overall very few missions are not completed, be it due to concurrent events or other, but studies have shown that for certain patient groups a large proportion of eligible patients do not receive a physician team response [ 27 ]. Also, ground ambulance HEMS missions are not included, which might affect in particular areas in and around the larger cities.…”
Section: Discussionmentioning
confidence: 99%
“…However, while population data are fairly stable, the same does not hold for incident data. The yearly reports on HEMS missions indicate that overall very few missions are not completed, be it due to concurrent events or other, but studies have shown that for certain patient groups a large proportion of eligible patients do not receive a physician team response [ 27 ]. Also, ground ambulance HEMS missions are not included, which might affect in particular areas in and around the larger cities.…”
Section: Discussionmentioning
confidence: 99%
“…[15] The challenge of the EMCC picking out the right resource for the right patient was recently discussed in a paper on the use of HEMS in Norway. [2] A study from 2013 showed that the EMCC assessment was downgraded in 42% of cases and upgraded in 11% of cases when the patient was seen by a GP. [9] The problem of under triage was also shown in a systematic review of telephone triage in out-of-hours care.…”
Section: Discussionmentioning
confidence: 99%
“…However, the capacity of the HEMS ambulance is limited, and most patients are handled by the casualty clinic GPs and EMTs alone. [1,2]…”
Section: Introductionmentioning
confidence: 99%
“…In Norway, four independent regions, each with one major trauma center, and an additional thirty-three acute care hospitals, form a national trauma system (29). In the South-Eastern Health Region, which is Norway's largest health region, the Oslo University Hospital (OUH) is the major trauma center.…”
Section: Contextmentioning
confidence: 99%